(untitled) (translation. a transdisciplinary journal, 2022)
Utterances are the products of actions, which like all actions, are undertaken for reasons. Understanding the reasons characteristic of other cultures and (as an instance of this) other times is part of what our teaching is about: this is especially important because in the easy atmosphere of relativism—in the world of ‘that’s just your opinion’ that pervades the high schools that produce our students—one thing that can get entirely lost is the rich differences of human life in culture.